Predicting the effect of vaccination of the transmission dynamics of heartwater (Cowdria ruminantium infection) - O'Callaghan, C.J.; Medley, G.F.; Peter, T.F.; Mahan, S.M.; Perry, Brian D. (International Society for Veterinary Epidemiology and Economics, 2000)
Heartwater, an infectious disease of ruminants caused by the rickettsia Cowdria ruminantium (transmitted by ixodid ticks of the genus Amblyomma and vertically), severely constrains livestock production throughout sub-Saharan Africa. Its epidemiology varies from epidemics with high mortality (on introduction into a previously unexposed population) through to endemic stability (very low morbidity when the vector density is high and host infection is common and occurs early in life). A new generation of inactivated vaccines for heartwater is being developed and there is an urgent need to investigate the impact of their use on transmission dynamics and livestock production economics as an aid in the design of cost-effective, integrated, control programmes. Without conducting long-term, expensive field trials, the only way of exploring these aspects is through predictive, quantitative models. A mathematical description of the trransmission dynamics of the tick-borne infection Cowdria ruminantium in commercial beef enterprises in Zimbabwe was used to consider the potential epidemiological impact of a candidate vaccine to prevent heartwater with the quantitative results employed in an economic analysis.